Catheter‐related blood stream infection caused by Mycobacterium chelonae in a child with myeloid leukemia associated with Down syndrome. Issue 2 (18th December 2020) - Fujikawa, Tomoko; Uemura, Suguru; Aoto, Yuya; Nambu, Yoshinori; Nagano, China; Nakatani, Naoko; Nino, Nanako; Yamamoto, Nobuyuki; Mori, Takeshi; Nishimura, Noriyuki; Iijima, Kazumoto
Abstract: Rapidly growing nontuberculous mycobacteria should be considered if GPRs gram‐positive rods are detected in blood cultures 2‐3 days after the blood sample collection. Abstract : Rapidly growing nontuberculous mycobacteria should be considered if GPRs gram‐positive rods are detected in blood cultures 2‐3 days after the blood sample collection.